MIM injection molding high-performance sintered samarium-iron-nitrogen magnet and preparation process thereof

By adding Nb to the surface of Sm2Fe17 powder through MIM injection molding to form a nano-modified layer, and combining it with gradient binder and three-stage nitriding process, the problems of shape complexity and density uniformity of samarium iron nitride magnets in traditional processes are solved, and high-performance samarium iron nitride magnets are prepared, which are suitable for miniaturized and precision products.

CN120796757AActive Publication Date: 2025-10-17동관 화옌 뉴 매터리얼 테크놀로지 씨오 엘티디

Patent Information

Application Number
CN202510970827.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-10-17
Estimated Expiration
2045-07-15

AI Technical Summary

Technical Problem

Traditional manufacturing processes are difficult to produce complex-shaped samarium iron nitride magnets, and the magnet density uniformity is poor. The diffusion efficiency of nitrogen atoms during nitriding is low, which limits the improvement of magnet coercivity and magnetic energy product, making it difficult to meet the needs of miniaturized and precision products.

Method used

High-performance samarium iron nitride magnets were prepared by using MIM injection molding process, adding Nb element to the surface of Sm2Fe17 powder to form an Nb nano-modified layer, combined with gradient binder and three-stage nitriding process.

Benefits of technology

It significantly improves the coercivity and magnetic stability of samarium iron nitride magnets, ensuring high density and uniformity of products, making them suitable for the manufacture of miniaturized and precision products, and enhancing the nitriding effect and magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to an MIM injection-molded samarium-iron-nitrogen magnet and a preparation process thereof.The preparation process comprises the steps that Nb is added into Sm2Fe17, a Nb nano-modified layer is formed through high-energy ball milling and heat treatment, then a degreased blank is obtained through a paraffin-polylactic acid-stearic acid ternary binder system with the mass ratio being 60: 30: 10 and gradient degreasing, and after the degreased blank is sintered, the MIM injection-molded samarium-iron-nitrogen magnet is obtained; nitriding treatment is carried out by adopting a three-stage process, and then the samarium-iron-nitrogen magnet with high magnetism is obtained after ultrasonic cleaning and other treatment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of injection molding of magnetic materials, and relates to a rare earth permanent magnet material, in particular to a MIM injection molded samarium iron nitrogen magnet and a preparation process thereof. BACKGROUND

[0002] At present, the permanent magnet material with the highest magnetic performance is a rare earth neodymium iron boron permanent magnet material, wherein the maximum magnetic energy product of sintered neodymium iron boron permanent magnet material has exceeded 56 MGOe, which is very beneficial to the miniaturization and lightening of devices, and in recent years has achieved wide application in the fields of wind power generation, new energy vehicles and elevators. However, the neodymium iron boron material has the defect of poor high-temperature resistance, which seriously limits its application in high-temperature fields.

[0003] The samarium iron nitrogen (Sm-Fe-N) magnet becomes an ideal material for replacing the neodymium iron boron magnet for application in a high-temperature environment due to high remanence, high coercivity and excellent temperature stability. The traditional preparation process usually adopts a powder metallurgy method, mixes Sm2Fe17 powder with a binder, and then performs pressing, degreasing, sintering and nitriding treatment to obtain the magnet. However, the traditional pressing process is difficult to prepare a complex-shaped component, and the magnet has poor density uniformity, and the nitrogen atom diffusion efficiency is low in the nitriding process, which limits the improvement of the coercivity and the magnetic energy product of the magnet.

[0004] The samarium iron nitrogen material becomes a strong competitor of the bonded neodymium iron boron magnetic powder due to the intrinsic magnetism superior to that of the neodymium iron boron, better oxidation resistance, higher Curie temperature and lower material cost, and has an irreplaceable role especially in the application in a high-temperature environment. The samarium iron nitrogen material is unstable at high temperatures and is prone to decomposition during sintering, and at present, the preparation and application of the bonded magnet are mainly adopted. This is mainly because the Sm2Fe17Nx compound is prone to irreversible decomposition when the temperature exceeds 550 DEG C, so it is difficult to prepare a dense magnet through the traditional sintering process. Therefore, the Sm2Fe17Nx compound is generally mixed with PA6, PA12 and other plastic binders at 200-300 DEG C for granulation and injection molding, and finally an injection molded magnet is prepared. Since a large amount of adhesive is added to the injection molded magnet, the material density and the magnetic performance are still lower than those of the sintered magnet.

[0005] With the continuous increase of the market of permanent magnet application, the products are required to be more miniaturized, precise and shaped. The processing difficulty of the products is also increasing. MIM is a metal injection molding (MIM) process, which has the characteristics of high precision and complex shape manufacturing capacity, and at the same time, the production efficiency is high and is suitable for large-scale production. Therefore, MIM samarium iron nitrogen has certain advantages in small and shaped products, but how to achieve the sintering density while ensuring the non-decomposition of N still needs to be studied.

[0006] Patent CN108766755A discloses a preparation method of anisotropic sintered SmFeN permanent magnet, which is obtained by first pressing Sm2Fe17 into a shape, orienting during the pressing process, and then sintering and nitriding; but the pressing process is only suitable for making single-oriented magnetic sheets or two-stage magnetic rings, and the size and structure of the product are greatly limited.

[0007] Patent CN111667967B discloses a high-fluidity SmFeN flexible bonded permanent magnet for injection molding and a preparation method thereof, which improves the melt fluidity of the SmFeN bonded magnet by optimizing the organic additive formula, facilitating the molding of devices with complex shape and large length-diameter ratio; but due to the mixing of the adhesive, the overall density of the magnet is large, so the magnetic performance is not high, and the maximum magnetic energy product is only 11 MGOe. SUMMARY

[0008] The present application provides a MIM injection molded SmFeN magnet and a preparation process thereof to solve the technical problems raised in the above background.

[0009] To achieve the above-mentioned application purposes, the present application adopts the following technical solutions:

[0010] In a first aspect, a preparation process of a MIM injection molded high-performance sintered SmFeN magnet comprises:

[0011] S1: Sm and Fe raw materials with a purity of ≥99.5% are prepared by vacuum induction melting to prepare Sm2Fe 17 alloy, crushed and sieved through a 200-400 mesh sieve to obtain initial powder with an average particle size of 50-80 μm, the powder is placed together with Nb powder with a mass fraction of 1%-3% and a particle size of ≤10 μm and ZrO2 ball milling medium with a mass fraction of 0.5%-1% in a planetary ball mill, and the Nb element is adsorbed on the surface of the Sm2Fe 17 powder under the protection of inert gas at a speed of 300-400 r / min for 8-12 h to form a preliminary mechanical mixing layer; the addition of Nb can inhibit the excessive growth of grains during sintering, and smaller grains can significantly improve the coercive force of the magnet; no subsequent nitriding process lays a good foundation for the substrate; the mechanical force of the ZrO2 ball milling medium activates the powder surface, increases the sphericity of the metal powder, and increases the adsorption capacity of the subsequent bonding agent.

[0012] S2: The mixed powder after ball milling is annealed at 700-780℃ for 2-3 hours to promote the diffusion of the Nb element to the grain boundaries and near-surface regions of Sm2Fe 17 , forming a stable Nb nano-modified layer, wherein the Nb element is in the form of Sm2Fe 17The grain boundary and near-surface region is gradient distribution, and the thickness of the Nb nano-modified layer is 100-150 nm; the Nb nano-modified layer is formed by two steps: first, mechanical alloying: under the protection of inert gas, Sm2Fe 17 alloy powder and Nb powder are subjected to high-energy ball milling, so that the Nb particles are embedded into the Sm2Fe 17 surface to form a preliminary mechanical mixing layer; second, heat treatment diffusion: the mixed powder after ball milling is annealed at 700-780℃ to promote the diffusion of Nb atoms to the Sm2Fe 17 grain boundary and near-surface region, forming a stable Nb nano-modified layer, which greatly improves the coercivity and magnetic stability.

[0013] S3: using a ternary binder system of paraffin-poly lactic acid-stearic acid with a mass ratio of 60:30:10, the pretreated Sm2Fe 17 powder is mixed with the binder at a solid content of 65%-70% by volume fraction, stirred at 120-150℃ and 50-80r / min for 3-5h to form a uniform feed, which is injected into the mold through a screw injection molding machine at 180-220℃ and an injection pressure of 80-120MPa, and cooled and demolded after pressure maintaining for 5-10s to obtain an injection molded body with a density of ≥90%, and at the same time, a pulse magnetic field is used to induce grain preferential orientation during injection molding, and the oriented magnetic field strength is 1-2T; the additive is selected to be a gradient binder system, poly lactic acid is used as a degradable carrier, which is preferentially decomposed during the debinding stage to form initial microporous channels, the low melting point property of paraffin ensures the flowability of the feed, and stearic acid improves the interfacial compatibility of the powder and the binder to reduce molding defects.

[0014] S4: solvent debinding: the injection molded body is placed in n-heptane solvent and ultrasonically oscillated at 50-60℃ for 4-6h to remove 60%-70% of the paraffin component to form a connected pore network;

[0015] S5: thermal debinding: the temperature is raised from room temperature to 400-500℃ at a rate of 5-8℃ / min, and the poly lactic acid is completely decomposed and volatilized in a nitrogen atmosphere for 2-5h, and the residual carbon content of the final debound body is ≤0.1%; a double-medium synergistic debinding process is adopted: solvent debinding forms preliminary channels, and gas can be discharged along the preset channels during thermal debinding, avoiding the bubbling and cracking problems of traditional single thermal debinding, and the size shrinkage rate of the debound body is controlled within 1.5%-2%. This debinding process is beneficial to the formation of fine micro-holes and channels in the matrix, which is beneficial to the permeation of nitrogen and improves the nitriding effect, and does not cause large deformation and shrinkage of the product, affecting the overall size.

[0016] S6: Put the defatted blank into a vacuum sintering furnace, and heat to 1000-1100℃ at a rate of 10℃ / min, and then heat for 2-3h, and then fill nitrogen or argon to a slight negative pressure, and then rapidly cool to room temperature by a fan, and in the sintering process, the Nb modification layer on the surface of the Sm2Fe17 powder forms a Nb-rich phase at the grain boundary, so that the average grain size is controlled to be 5-10μm, and the grain boundary is clear and uniform;

[0017] S7: Put the sintered blank into a high-pressure nitriding furnace, and adopt a three-stage process:

[0018] Low-temperature adsorption stage: temperature 450-500℃, ammonia pressure 0.5-1MPa, heat preservation time 0.5-3h, so that N atoms are physically adsorbed on the surface of the magnet and form an initial nitriding layer;

[0019] Medium-temperature diffusion stage: heat to 550-600℃, ammonia pressure is reduced to 0.2-0.3MPa, heat preservation time 0.5-3h, use the concentration gradient to promote the diffusion of N atoms to the inside, while avoiding grain coarsening at high temperature;

[0020] High-temperature solid solution stage: heat to 650-700℃, and pass in N2 and H2 mixed gas according to a volume ratio of 3:1, pressure 1-1.5MPa, heat preservation time 0.5-3h, so that N atoms are fully solid-solved in the Sm2Fe 17 lattice to form a stable Sm2Fe17N3-x phase; adopt a three-stage process: low-temperature adsorption stage, medium-temperature diffusion stage, and high-temperature solid solution stage, so that the nitriding depth is increased to 50-80μm, and the nitrogen content is uniformly distributed (N atom fraction 8%-10% on the surface, and 6%-8% in the core).

[0021] S8: ultrasonic cleaning of the nitrided magnet to remove surface residual impurities, then physical vapor deposition to coat an Al2O3 protective layer with a thickness of 5-10μm, and finally electric spark cutting to the required size to obtain the final Sm-Fe-N magnet.

[0022] Further, the inert gas in S1 is argon or nitrogen.

[0023] Further, the temperature of the annealing treatment in S2 is 750℃, and the heat preservation time is 2.5 hours.

[0024] Further, the thickness of the Nb nano-modification layer in S2 is 130nm.

[0025] Further, in S6, the Nb modification layer on the surface of the Sm2Fe 17 powder forms a Nb-rich phase at the grain boundary, so that the average grain size is controlled to be 8μm.

[0026] Further, the thickness of the Al2O3 protective layer in S8 is 8μm.

[0027] The second aspect is a Sm-Fe-N magnet prepared by the preparation process of the MIM injection molding high-performance sintered Sm-Fe-N magnet.

[0028] The beneficial effects of the present application over the prior art are:

[0029] 1. The present application can inhibit the excessive growth of grains during sintering by adding Nb, and smaller grains can significantly improve the coercivity of the magnet; the excellent substrate foundation is laid without subsequent nitriding process; the mechanical force of ZrO2 ball milling medium promotes the surface activation of the powder, increases the sphericity of the metal powder, and increases the adsorption capacity of the subsequent binder.

[0030] 2. The present application adopts two steps to form the Nb nano-modified layer, the first step is mechanical alloying: under the protection of inert gas, Sm2Fe 17 alloy powder and Nb powder are high-energy ball milled to embed Nb particles into the surface of Sm2Fe 17 to form a preliminary mechanical mixing layer; the second step is heat treatment diffusion: the mixed powder after ball milling is annealed at 700-780℃ to promote the diffusion of Nb atoms to the grain boundary and near-surface area of Sm2Fe 17 to form a stable Nb nano-modified layer; if only ball milling is used when forming the Nb nano-modified layer, the mechanical alloying only realizes the physical embedding of Nb particles, without forming atomic-level diffusion, resulting in uneven distribution of Nb and discontinuous modified layer, and limited improvement of coercivity; if only heat treatment is used when forming the Nb nano-modified layer, the diffusion rate of Nb is low, and the improvement of coercivity is not ideal. The present application adopts two steps to form the Nb nano-modified layer, which overcomes the technical problems of poor coercivity and unstable magnetism in the prior art, and greatly improves the coercivity and magnetic stability.

[0031] 3. The present application selects a gradient binder system as an additive, polylactic acid is used as a degradable carrier, which is preferentially decomposed in the debinding stage to form initial microporous channels, the low melting point property of paraffin ensures the flowability of the feed, and stearic acid improves the interfacial compatibility of the powder and the binder to reduce molding defects.

[0032] 4. The present application adopts a double-medium cooperative debinding process: solvent debinding forms initial pores, and gas can be discharged along the pre-set channels during thermal debinding, avoiding the problems of bubbling and cracking in traditional single thermal debinding, and the size shrinkage rate of the green body after debinding is controlled within 1.5%-2%. This debinding process is beneficial to the formation of fine micro-pores and channels in the substrate, which is beneficial to the penetration of nitrogen and improves the nitriding effect, and also does not cause large deformation and shrinkage of the product, affecting the overall size.

[0033] 5. Compared with the traditional nitriding under single temperature and pressure, the diffusion depth of nitrogen atoms is only 5-10μm. The present invention adopts segmented control, places the sintered green body into a high-pressure nitriding furnace, and adopts a three-stage process: low-temperature adsorption stage, medium-temperature diffusion stage, and high-temperature solid solution stage, so that the nitriding depth is increased to 50-80μm, and the nitrogen content is evenly distributed (the N atomic fraction in the surface layer is 8%-10%, and the core is 6%-8%). DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually illustrative and is in no way intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.

[0036] Unless otherwise specifically stated, the relative arrangement of the parts and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention. Technology, methods and equipment known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments can have different values. It should be noted that similar numbers and letters represent similar items below, and therefore, once an item is defined, it is not necessary to discuss it further subsequently.

[0037] Example 1:

[0038] A preparation process for a high-performance sintered samarium iron nitrogen magnet by MIM injection molding, comprising:

[0039] S1:Sm2Fe 17 Alloy powder pretreatment: Sm and Fe raw materials with a purity of ≥99.5% are prepared by vacuum induction melting to produce Sm2Fe 17alloy, crushed and sieved through a 250 mesh screen to obtain an initial powder with an average particle size of 55 μm. The powder was placed in a planetary ball mill together with 1% by mass of Nb powder (average particle size = 8 μm) and 1% of ZrO2 ball milling medium, and ball milled at 300 r / min for 10 h under argon protection, so that the Nb element was adsorbed on the surface of the Sm2Fe 17 powder, forming a preliminary mechanical mixing layer; the addition of Nb can inhibit the excessive growth of grains during sintering, and smaller grains can significantly improve the coercivity of the magnet; no subsequent nitriding process lays a good foundation for the substrate; the mechanical force of the ZrO2 ball milling medium promotes the activation of the powder surface, increases the sphericity of the metal powder, and increases the subsequent adsorption capacity of the binder.

[0040] S2: The mixed powder after ball milling was annealed at 750°C for 2.5 h to promote the diffusion of the Nb element to the Sm2Fe 17 grain boundary and near-surface region, forming a stable Nb nano-modified layer, wherein the Nb element is distributed in the Sm2Fe 17 grain boundary and near-surface region in a gradient distribution, and the thickness of the Nb nano-modified layer is 130 nm; the Nb nano-modified layer adopts two steps, the first step is mechanical alloying: under the protection of inert gas, Sm2Fe 17 alloy powder and Nb powder are ball milled at high energy, so that the Nb particles are embedded in the Sm2Fe 17 surface, forming a preliminary mechanical mixing layer; the second step is heat treatment diffusion: the mixed powder after ball milling is annealed at 750°C to promote the diffusion of the Nb atoms to the Sm2Fe 17 grain boundary and near-surface region, forming a stable Nb nano-modified layer, which greatly improves the coercivity and magnetic stability.

[0041] S3: A ternary binder system of paraffin-poly lactic acid-stearic acid with a mass ratio of 60:30:10 was used to mix the pretreated Sm2Fe 17 powder and the binder at a solid content of 65% by volume fraction, stirred at 150°C and 80 r / min for 3 h to form a uniform feed, and then injected into a mold at 195°C and an injection pressure of 120 MPa through a screw injection molding machine, cooled and demolded after pressure maintaining for 10 s to obtain an injection molded body with a density of ≥90%, and at the same time, a pulse magnetic field was used to induce grain preferential orientation during the injection molding process, with an orientation magnetic field strength of 1.52 T; a gradient binder system was added as an auxiliary agent, poly lactic acid was used as a degradable carrier, which was preferentially decomposed during the debinding stage to form initial microporous channels, the low melting point characteristic of paraffin ensured the flowability of the feed, and stearic acid improved the interfacial compatibility between the powder and the binder, reducing molding defects.

[0042] S4: Solvent debinding: the injection molded body was placed in n-heptane solvent and ultrasonically oscillated at 50°C for 4 h to remove 60% of the paraffin component, forming a connected pore network;

[0043] S5: heat debinding: increasing the temperature from room temperature to 400℃ at a rate of 5℃ / min, keeping for 2h in nitrogen atmosphere, so that polylactic acid is completely decomposed and volatilized, and the residual carbon content of the final debound blank is ≤0.1%; a double-medium synergistic debinding process is adopted: solvent debinding forms initial pores, and gas can be discharged along the preset channels during heat debinding, avoiding the problems of bubbling and cracking in traditional single heat debinding, and the size shrinkage rate of the blank after debinding is controlled within 1.5%-2%. This debinding process is beneficial to the formation of fine micro-pores and channels in the matrix, which is conducive to the penetration of nitrogen and improves the nitriding effect, and does not cause large deformation and shrinkage of the product, affecting the overall size.

[0044] S6: placing the debound blank into a vacuum sintering furnace, increasing the temperature to 1100℃ at a rate of 10℃ / min, keeping for 2h, then filling nitrogen or argon to micro-negative pressure, and then rapidly cooling to room temperature by a fan, during the sintering process, Sm2Fe 17 The Nb modified layer on the surface of the powder forms a Nb-rich phase at the grain boundary, so that the average grain size is controlled within 5-10μm, and the grain boundary is clear and uniform;

[0045] S7: placing the sintered blank into a high-pressure nitriding furnace, and adopting a three-stage process:

[0046] low-temperature adsorption stage: temperature 450℃, ammonia pressure 1MPa, keeping for 1h, so that N atoms are physically adsorbed on the surface of the magnet and form an initial nitrided layer;

[0047] medium-temperature diffusion stage: increasing the temperature to 550℃, reducing the ammonia pressure to 0.2MPa, keeping for 2h, using the concentration gradient to promote the diffusion of N atoms to the interior, while avoiding grain coarsening at high temperature;

[0048] high-temperature solid solution stage: increasing the temperature to 650℃, and introducing N2 and H2 mixed gas according to a volume ratio of 3:1, pressure 1MPa, keeping for 1h, so that N atoms are fully solid-solved in the Sm2Fe17 lattice to form a stable Sm2Fe17N3-x phase; adopting a three-stage process: low-temperature adsorption stage, medium-temperature diffusion stage, and high-temperature solid solution stage, so that the nitriding depth is increased to 50-80μm, and the nitrogen content is uniformly distributed (N atom fraction 8%-10% on the surface, and 6%-8% in the core).

[0049] S8: ultrasonic cleaning the nitrided magnet to remove surface residual impurities, then coating an Al2O3 protective layer with a thickness of 8μm by physical vapor deposition, and finally processing to the required size by electric spark cutting to obtain the final Sm-Fe-N magnet.

[0050] Comparative Example 1:

[0051] The present comparative example provides a preparation process of MIM injection molding high-performance sintered samarium iron-nitrogen magnet, comprising the following steps, the difference between the present comparative example and example 1 is only that no Nb element is added in S1, step S2 is missing, and the rest is the same as example 1.

[0052] Comparative example 2:

[0053] The present comparative example provides a preparation process of MIM injection molding high-performance sintered samarium iron-nitrogen magnet, comprising the following steps, the difference between the present comparative example and example 1 is only that ball milling is performed in S1, and the rest is the same as example 1.

[0054] Comparative example 3:

[0055] The present comparative example provides a preparation process of MIM injection molding high-performance sintered samarium iron-nitrogen magnet, comprising the following steps, the difference between the present comparative example and example 1 is only that step S2 is missing, and the rest is the same as example 1.

[0056] Comparative example 4:

[0057] The present comparative example provides a preparation process of MIM injection molding high-performance sintered samarium iron-nitrogen magnet, comprising the following steps, the difference between the present comparative example and example 1 is only that a single binder is used in step S3, step S4 is missing, and the rest is the same as example 1.

[0058] Comparative example 5:

[0059] The present comparative example provides a preparation process of MIM injection molding high-performance sintered samarium iron-nitrogen magnet, comprising the following steps, the difference between the present comparative example and example 1 is only that a single temperature and pressure is used in step S7, and the rest is the same as example 1.

[0060] The comprehensive performance of the MIM samarium iron-nitrogen magnets obtained in example 1 and comparative examples 1-5 is as follows:

[0061]

[0062] It is shown from the above embodiment 1 and comparative examples 1-4 that the remanence of the samarium iron nitride magnet prepared by the preparation process of the MIM injection molding high-performance sintered samarium iron nitride magnet is 10.7 KGs, the coercive force is 15.2 KOe, and the magnetic energy product is 29 MGOe. The samarium iron nitride magnet has excellent magnetic properties. Compared with comparative example 1 and embodiment 1, the addition of Nb significantly improves the coercive force and magnetic energy product of the samarium iron nitride magnet, so that the samarium iron nitride magnet has excellent magnetic properties. It is shown from comparative example 2 and comparative example 3 that when the Nb nano-modified layer is formed, if only ball milling is used when the Nb nano-modified layer is formed in comparative example 2, the mechanical alloying only realizes the physical embedding of the Nb particles, and atomic diffusion is not formed, resulting in uneven distribution of Nb and discontinuous modified layer, and the coercive force is limited, and the coercive force is only 8.5 KOe. If only heat treatment is used when the Nb nano-modified layer is formed in comparative example 3, the diffusion rate of Nb is low, and the improvement of the coercive force is not ideal, and the coercive force is only 10.2 KOe. The present application forms the Nb nano-modified layer in two steps, which overcomes the technical problems of poor coercive force and unstable magnetism in the prior art, and greatly improves the coercive force and the stability of the magnetism.

[0063] The preparation process of the MIM injection molding high-performance sintered samarium iron nitride magnet in the present application: adding Nb element in Sm2Fe 17 The preparation process of the MIM injection molding high-performance sintered samarium iron nitride magnet in the present application: adding Nb element in Sm2Fe

[0064] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A process for preparing high-performance sintered samarium iron nitrogen magnets by MIM injection molding, characterized by: S1: Prepare Sm2Fe by vacuum induction melting of Sm and Fe raw materials with a purity of ≥99.5% 17 The alloy is crushed and passed through a 200-400 mesh sieve to obtain an initial powder with an average particle size of 50-80 μm. The powder is put into a planetary ball mill together with 1%-3% by mass of Nb powder with a particle size of ≤10 μm and 0.5%-1% by mass of ZrO2 ball milling media. The ball mill is milled at 300-400 r / min for 8-12 hours under the protection of inert gas to allow the Nb element to be adsorbed on the Sm2Fe 17 On the surface of the powder, a preliminary mechanical mixing layer is formed; S2: The ball-milled mixed powder is annealed at 700-780°C for 2-3 hours to promote the transfer of Nb elements to Sm2Fe 17 The Nb element diffuses into the grain boundary and near surface area to form a stable Nb nano-modified layer, in which the Nb element is present in the Sm2Fe 17 The grain boundaries and near-surface regions show a gradient distribution, and the thickness of the Nb nano-modified layer is 100–150 nm; S3: Using a paraffin wax-polylactic acid-stearic acid ternary binder system with a mass ratio of 60:30:10, the pretreated Sm2Fe 17 The powder and the binder are mixed at a solid phase content of 65% to 70% by volume, stirred at 120-150°C and 50-80r / min for 3-5h to form a uniform feed, and injected into the mold through a screw injection molding machine at 180-220°C and an injection pressure of 80-120MPa. After holding the pressure for 5-10s, the mold is cooled and demolded to obtain an injection molded body with a density of ≥90%. At the same time, during the injection molding process, a pulsed magnetic field is used to induce preferential grain orientation, and the orientation magnetic field intensity is 1-2T. S4: Solvent degreasing: Place the injection molded body in n-heptane solvent and ultrasonically vibrate at 50-60°C for 4-6 hours to remove 60%-70% of the paraffin components and form a connected pore network; S5: Thermal debinding: Heating the temperature from room temperature to 400-500°C at a rate of 5-8°C / min, and keeping the temperature in a nitrogen atmosphere for 2-5 hours to completely decompose and volatilize the polylactic acid. The final residual carbon content of the degreased body is ≤0.1%; S6: Place the degreased body into a vacuum sintering furnace, heat it to 1000-1100℃ at 10℃ / min, keep it warm for 2-3h, fill it with nitrogen or argon to a slight negative pressure, and then quickly cool it to room temperature with a fan. During the sintering process, Sm2Fe 17 The Nb modified layer on the powder surface forms a Nb-rich phase at the grain boundaries, which controls the average grain size to 5-10μm and makes the grain boundaries clear and uniform; S7: Place the sintered body into a high-pressure nitriding furnace using a three-stage process: Low temperature adsorption stage: temperature 450-500℃, ammonia pressure 0.5-1MPa, heat preservation 0.5-3h, so that nitrogen atoms are physically adsorbed on the magnet surface and form an initial nitride layer; Medium-temperature diffusion stage: the temperature is raised to 550-600°C, the ammonia pressure is reduced to 0.2-0.3 MPa, and the temperature is kept for 0.5-3 hours. The concentration gradient is used to promote the diffusion of nitrogen atoms into the interior, while avoiding grain coarsening at high temperatures. High temperature solid solution stage: heat to 650-700℃, introduce N2 and H2 mixed gas in a volume ratio of 3:1, pressure 1-1.5MPa, keep warm for 0.5-3h, so that N atoms are fully dissolved in Sm2Fe 17 lattice, forming a stable Sm2Fe 17 N 3-x Mutually; S8: The nitrided magnet is ultrasonically cleaned to remove residual impurities on the surface, and then coated with a 5-10 μm thick Al2O3 protective layer by physical vapor deposition. Finally, it is processed by electric spark cutting to the required size to obtain the final SmFeN magnet.

2. The preparation process of a MIM injection molded high performance sintered samarium iron nitrogen magnet according to claim 1, characterized in that: in, The inert gas in S1 is argon or nitrogen.

3. The preparation process of a MIM injection molded high performance sintered samarium iron nitrogen magnet according to claim 1, characterized in that: in, The temperature of the annealing treatment in S2 is 750° C., and the holding time is 2.5 hours.

4. The preparation process of a MIM injection molded high performance sintered SmFeN magnet according to claim 1, characterized in that: in, The thickness of the Nb nano-modified layer in S2 is 130 nm.

5. The preparation process of a MIM injection molded high performance sintered samarium iron nitrogen magnet according to claim 1, characterized in that: in, The S6Sm2Fe 17 The Nb-modified layer on the powder surface forms a Nb-rich phase at the grain boundaries, which controls the average grain size to 8 μm.

6. The process for preparing a MIM injection molded high performance sintered SmFeN magnet according to claim 1, characterized in that: in, The thickness of the Al2O3 protective layer in S8 is 8 μm.

7. A samarium iron nitrogen magnet prepared by the process for preparing a high-performance sintered samarium iron nitrogen magnet by MIM injection molding according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of metal powder injection molding sintered rare earth magnet

    CN117133538A

  • MIM injection molding process of neodymium-iron-boron magnet

    CN119092286A

  • Rare-earth bonded magnet, material therefor and method for manufacturing a bonded magnet

    EP0549149A1

  • Alloy-powder for rare earth-transition metal permanent magnet

    JP1994151130A

  • Manufacture of r-fe-b series sintering magnet by injection molding

    JP1994168810A

Cited By

  • Multi-field linkage injection molding method of magnet

    CN121199105A

  • Multi-field linkage injection molding method of a magnet

    CN121199105B